2015
DOI: 10.1039/c5sm01216c
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization and magnetic behavior of a spin-labelled physical hydrogel containing a chiral cyclic nitroxide radical unit fixed inside the gelator molecule

Abstract: An optically active amphiphilic nitroxide radical compound [(S,S,R)-], which contains a paramagnetic (2S,5S)-2,5-dimethyl-2,5-diphenylpyrrolidine-N-oxyl radical group fixed in the inner position together with a hydrophobic long alkyl chain and a hydrophilic (R)-alanine residue in the opposite terminal positions, was found to serve as a low-molecular-weight gelator in H2O to give rise to a spin-labelled physical hydrogel. Characterization of the hydrogel was performed by microscopic (SEM, TEM and AFM) technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
(64 reference statements)
0
9
0
Order By: Relevance
“…Few EPR studies reported in the literature regard the supramolecular gels resulting from assembly of LMWG [109][110][111][112]. One explanation is probably that the self-assembly process represents a reorganization and thus selective process and insertion of a different molecule in the fibrillar assembly is, in general, less probable.…”
Section: Epr Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Few EPR studies reported in the literature regard the supramolecular gels resulting from assembly of LMWG [109][110][111][112]. One explanation is probably that the self-assembly process represents a reorganization and thus selective process and insertion of a different molecule in the fibrillar assembly is, in general, less probable.…”
Section: Epr Spectroscopymentioning
confidence: 99%
“…Takemoto et al [110] reported the synthesis of an amphiphilic optically active compound that contains a paramagnetic (2S,5S)-2,5-dimethyl-2,5-diphenylpyrrolidine-N-oxyl radical fixed in the inner position with a hydrophobic long chain and a hydrophilic R-alanine residue in the opposite terminal position. They found that this compound acted as a LMWG in water, resulting in a spin-labelled hydrogel.…”
Section: Epr Spectroscopymentioning
confidence: 99%
“…Compared to other traditional stimuli such as pH and temperature, the magnetic response is more suitable for controlling delivery due to its unique features including remote operation, fast response and easily controlled manipulation . Previous studies indicated that magnetic field‐sensitive hydrogels can be easily prepared by the introduction of magnetic nanoparticles (MNPs) or other organic ferromagnets into hydrogel matrices . MNPs are of great interest from a wide range of aspects, including magnetic resonance imaging, magnetocaloric effect, catalysis, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was reported that amino acid based gelators containing a stable organic radical moiety form fibrous aggregates in organic solvent and aqueous solution . The fibrous aggregates exhibited paramagnetic properties with antiferromagnetic interactions.…”
Section: Introductionmentioning
confidence: 99%
“…[7c] Recently,i tw as reported that amino acid basedg elators containing as table organic radical moiety [12] form fibrousa ggregates in organic solvent [13] and aqueous solution. [14] The fibrous aggregates exhibited paramagnetic properties with antiferromagnetic interactions. This observation suggestst hat selfassemblyo fg elators is ap romising approach to control of magnetic properties of stable organicr adicals.…”
Section: Introductionmentioning
confidence: 99%